Comparison of the Effects of Repetitive Transcranial Magnetic Stimulation and Aerobic Exercise as an Adjunct Therapy in Depressed Patients on Activity of Daily Living and Quality of Life - Muhammad Yusuf; Sri Mardjiati Mei Wulan; Reni Hendrarati Masduchi; Agustina Konginan (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: Depression is one of the most common causes of disabilities and poor quality of life worldwide. One-fifth of patients fail to respond to antidepressant therapy. Hence, adjunct therapy is urgently needed. Aim: This study aims to compare the effectiveness of repetitive transcranial magnetic stimulation (rTMS) and aerobic exercise as adjunct therapy on activity of daily living and quality of life in depressed patients. Material and Methods: A randomized-controlled experiment was conducted between May 2019 and January 2020. Twenty-seven depressed patients were divided into three groups for two weeks: antidepressant-only, antidepressant-and-aerobic exercise, and antidepressant-and-rTMS. The Barthel Index and SF-36 were used to assess the activity of daily living and quality of life. Results: After the intervention, there were no appreciable changes in the Barthel Index scores in any of the three groups (p>0.05). Following therapy, SF-36 results for physical function, bodily discomfort, public health, vitality, social function, emotional role functioning, and mental health all showed substantial improvements across groups (p 0.05). Patients in the antidepressant and rTMS groups improved more than those in the other two groups in the areas of overall health (15.71±6.075, p=0.009), emotional role functioning (20.29±11.940, p=0.049), and mental health (14.29±6.075, p=0.041). However, the Barthel Index score changes did not differ between groups (p=0.664). Conclusion: Better quality of life improvement in the rTMS group compared to the other two groups supports the use of rTMS as an additional therapy. It aims to enhance quality of life in patients with moderate and severe first-episode depression.